Strategi Media Relations Humas dalam Membangun Citra Positif Pemerintah Kota Bekasi - Annisa, Fitria Nur (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
This study aims to determine the media relations strategy carried out by the Public Relations of the Bekasi City Regional Secretariat in building good relations with the media using the concept of media relations strategy from Yosal Iriantara. This study uses a descriptive-qualitative method with data collection techniques through in-depth interviews, observation, and documentation. The result of the research is that the media relations strategy carried out by the Public Relations of the Bekasi City Regional Secretariat consists of three processes. First, the process of managing relationships by establishing partnerships with the media, selecting and selecting the right media, and carrying out media relations activities. Second, the process of developing a strategy by using various media in conveying messages, establishing and maintaining contact with the media, and positioning oneself as a reliable source of information for the media. Third, the process of developing a network by establishing relationships with professional journalist organizations and collaborating with journalist professional organizations and the West Java Provincial Government Public Relations.